SHARIA COMPLIANCE IN THE CAPITAL MARKET: REGULATION, IMPLEMENTATION, AND CHALLENGES - Yus Hermansyah; Djenal Suhara; Hasanudin; Dudi Badruzaman; Ahmad Rudiansyah (International Conference on Health Science, Green Economics, Educational Review and Technology, 2022)
A lack of awareness of the benefits and potential profits of Sharia investment can hinder the growth of the Sharia capital market. Efforts are needed to harmonize sharia regulations and clarify the standards that must be complied with by capital market participants. The purpose of this study is to analyze the regulations, implementation, and challenges of Sharia compliance in the capital market. The research method used is qualitative descriptive. The data collection techniques used are observation and documentation with interpretive data analysis. The results of the study show that clear, comprehensive, and responsive regulations to market developments can be a strong foundation for business and investment practices that are in accordance with Sharia principles. The implementation of Sharia principles in business and investment practices requires a strong commitment from all stakeholders. Challenges in maintaining Sharia compliance in the capital market include the complexity of financial instruments, different understandings of Sharia principles, transparency and reporting that still need to be improved, as well as the challenges of effective supervision and law enforcement. Awareness and education of Sharia principles among stakeholders is essential to increase understanding, transparency, and compliance. Ongoing education on sharia compliance can help address some of the challenges faced.